Pengaruh Infusa Daun Sambiloto (Andrographis paniculata Nees) Terhadap Pertumbuhan Bakteri Shigella dysenteriae Secara In Vitro - Fitri Nadifah; Siti Fatimah; Indah Yuliana Barekola Lamablawa (Journal of Health (JoH), 2014)
Background: Bacteria Shigella dysenteriae is pathogenic bacterium which cause diarrheal diseases that enter into inside the body through intestine. Shigella dysenteriae constitute one of the gram negative bacterium which causes inflammation on intestinal, pain abdominal, tenesmus, and a bowel movements which accompanied with blood and mucus. Bad impact irational use of synthethic drugs and antibiotics can cause organ damage and germs resistance. Utilization of herbs as traditional medicine evolving rapidly and alternatively used by most. Traditional medicine has relatively low of side effect and affordable prices. Sambiloto (Andrographis paniculata Nees) is a plant which is ordinary used as a traditional medicine that can easily found around Indonesian islands. Sambiloto constitute one of the medicinal plants which is allegedly has the antibacterial effect because its chemical content of flavonoid saponins and tannin. The objective of this study is to know the influence of sambiloto (Andrographis paniculata Nees) leaves infuse against the growth of Shigella dysenteriae bacteria. Method: This is an experimental research using diffusion method. Statistical test who used namely analysis of variant one road (One Way anova). Analysis data were done descriptively and statistically and presented with of tables or graphs. Results: There is influence of sambiloto leaf infusa (Andrographis paniculata Nees) against the growth of Shigella dysenteriae bacteria in vitro with a mean diameter zone of radical on concentrations the smallest 20% is 12 mm and the greatest concentration 100% is 24.3 mm. Conclusion: Infuse leaf has a strong and positive influence in inhibit the growth of bacteria Shigella dysenteriae bacterium.